2022
DOI: 10.3390/ijms23169064
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Fatty Acid Synthase in Lipid Metabolism and Metamorphic Development in a Destructive Insect Pest, Spodoptera litura (Lepidoptera: Noctuidae)

Abstract: Fatty acid synthase (FAS) is a key enzyme in the lipid synthesis pathway, however, its roles in insects remain largely unknown. Here, we firstly identified two FAS genes from the transcriptome dataset of the general cutworm Spodoptera litura, which is a destructive insect pest of many crops. Both SlFAS1 and SlFAS2 were highly expressed in third instar larvae and in their fat bodies. Then, we successfully silenced SlFAS1 in third instar larvae and the content of α-linolenic acid and triglyceride was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…However, for BSF itself, cellular function of LA and its derivates have not been characterized. Due to knock down or knock out of HiFAS may cause growth defects as happened in other insects (Pei et al, 2019; Song et al, 2022), which may cover the consequential phenotypes of immunity impairment if LA and its derivates participate in BSF nonspecific immunity beyond its function in energy storage. Transgenic fruit fly loaded with HiFAS, act as in vitro , may detour these problems and reveal the biological function of LA in BSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for BSF itself, cellular function of LA and its derivates have not been characterized. Due to knock down or knock out of HiFAS may cause growth defects as happened in other insects (Pei et al, 2019; Song et al, 2022), which may cover the consequential phenotypes of immunity impairment if LA and its derivates participate in BSF nonspecific immunity beyond its function in energy storage. Transgenic fruit fly loaded with HiFAS, act as in vitro , may detour these problems and reveal the biological function of LA in BSF.…”
Section: Discussionmentioning
confidence: 99%
“…In insects, the ability of DNL was long thought to be ubiquitous as other animals. There were thus little reports about fatty acid biosynthesis or DNL related enzyme activity in last decades and more work was focused on physiological phenotypes in insects, including growth, development, oviposition, and desiccation tolerance (Alabaster et al, 2011;Chung et al, 2014;Li et al, 2016;Moriconi et al, 2019;Parvy et al, 2012;Pei et al, 2019;Song et al, 2022). One hot spot of DNL research in insects was about the ability of lipid synthesis in wasps due to their parasitic lifestyle (Prager et al, 2019;Visser et al, 2017Visser et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Pablo et al’s research showed that the development of the Mediterranean fruit fly ( Ceratitis capitata ) is regulated by changes in oxygen consumption rates and the levels of primary energy molecules, such as lipids, glycogen, and trehalose. Yan et al analyzed the expression patterns and functions of fatty acid synthase genes ( SlFAS1 and SlFAS2 ) in the larvae of the tobacco cutworm ( Spodotera litura ), demonstrating the crucial role of fatty acid synthesis and storage in insects’ metabolism and metamorphic development [ 43 , 44 ]. These findings support the results observed in this study of the developmental delays in B. dorsalis larvae under hypoxic conditions, as depicted in Figure 2 (A(1)–A(3)); the decreased pupation rate and hindered emergence, as shown in Figure 2 (B(1)–B(3)), suggest that IR further impairs metabolic activity in insects, thereby hindering their normal development within the expected timeframe.…”
Section: Discussionmentioning
confidence: 99%
“…The gene EVM0003865 (fatty acid synthase) was identified as the putative target for miR-34-5p in combination of software prediction and negative regulation analysis of miRNA-mRNA (Tables S9). In Spodoptera litura, silencing SlFAS1 in larvae resulted in a significant decrease in the content of alpha-linolenic acid and triglyceride with more malformed pupae and adults, and the emergence rates were significantly reduced (Song et al, 2022), Hence, the gene EVM0003865 may be involved in deutonymph-adult transition by regulating lipid transport and metabolism. Meanwhile, the gene EVM0000927 (ABC transporter G family member 20-like) was identified as the putative target for miR-305-5p applying the same approach (Tables S9).…”
Section: Discussionmentioning
confidence: 99%